Electronic Media Device Usage and Its Associations With BMI and Obesity in a Rapidly Developing City in South China - Qiu, Ying; Xie, Yao Jie; Chen, Liping; Wang, Shao Ling; Yang, Hualu; Huang, Zhenzhen; Liu, Ping; Mo, Beirong (Frontiers in Public Health, 2021)
Objective This study aimed to evaluate the television (TV) viewing and computer and mobile phone usage duration in a community sample of Chinese adults and examine their associations with BMI and obesity. Method We conducted a community-based health needs assessment study from February to December of 2018 amongst 2873 Chinese adults in Nanshan District of Shenzhen, China. We used self-administered questionnaires to collect the data from 24 community health service centres in Nanshan District. The participants individually recorded the time they spent watching TV and using computers and mobile phones. They also answered questions about their socio-demographic and lifestyle factors. We measured their height and weight by using ultrasonic height and weight scales. Then, we calculated and categorised their BMI in accordance with the standards prescribed by the World Health Organization for Asians. Results Most of the participants were young adults (aged 18-44 years, 74.2%). The overall prevalence of obesity was 15.30%. The prevalence of TV, computer and mobile phone usage was 75.5%, 71.2% and 93.8% in females and 71.1%, 75.7% and 94.2% in males, respectively. The youth (18-24 years) and the elderly (65 years and above) had the longest time using mobile phones (3.78±2.51 hours) and watching TV programmes (2.12±1.38 hours), respectively. Longer usage of computers and mobile phones were evident in males (p <0.05) and participants with a high education level (p<0.01). The univariate analysis results showed an association between high BMI and obesity and short duration of using computers and mobile phones (all p<0.05). By contrast, no significant associations found between the length of TV programme viewing and mobile phone usage and BMI (p>0.05). After we adjusted for potential confounders, we found that computer usage time and the overall usage time of the three electronic devices had an inverse association with BMI (p<0.05). Conclusions Mobile phones were the most popular electronic device in Nanshan residents of Shenzhen. Unlike most previous studies, we found an inverse association between screen time and BMI. Nevertheless, scholars should conduct further studies to explore this association. Overall, we strongly encourage the appropriate use of electronic devices.